DID EUROPEAN COUNTRIES SUFFER FROM DIFFERENT CALCULATION OF HDI? - Maria-Lenuta CIUPAC-ULICI (Studia Universitatis Babeş-Bolyai Negotia, 2015)
The Human development index (HDI) was introduced for the first time in the summer of 1990. The objective was to provide a more complex indicator that captures a country`s development level better than the gross national product. UNDP (United Nations Development Programme) justified this approach by the need to attempt to provide an informative value that exceeds the strict quantitative aspects. This article analyzes the impact of different calculation of HDI, by comparing the values of the index calculated relying on the Human Development Report from 2005 with the values of the index calculated based on the Human Development Report from 2010 for 10 European countries (five emerging countries and five developed countries). When using the new methodology in calculating the Human Development Index, there is a small and insignificant difference. The HDI values obtained based on the new methodology from the Human Development Report from 2010 are smaller, but these values do not change their rank.